Pengaruh Aktivitas Jasmani melalui Sepak Bola terhadap Kepercayaan Diri Orang dengan HIV Positif - Nadia Eka Putri (Institut Teknologi Bandung, 2022)
Abstract Self-confidence is a feeling of confidence in one's abilities without fear and being able to solve all life's challenges without comparing them with the abilities of others. This statement does not apply to people with HIV-positive because the stigma attached to them by society, such as groups of sinners, guilty, recipients of curses, and even torment, lower their self-confidence of people with HIV-positive. Physical activity through football has an important role in changing stigma and is a way for people with HIV-positive to be accepted by society regardless of their status. This study aims to determine the effect of physical activity through football on the self-confidence of people with HIV-positive. The research uses causal-comparative or ex post facto research methods. Sampling used a purposive sampling technique with a sample of 5 people with HIV-positive who participated in football activities. The instrument used is a closed questionnaire using a Likert Scale. Based on the validity test of a valid questionnaire as many as 28 items out of 50 statement items and reliability test results obtained 0.722021 and included in the reliable criteria. Processing and analyzing data, it was found that the score of people with HIV-positive who took part in football activities was 514 from a maximum score of 700 after the percentage of the results was 73.43%. Thus, researchers can conclude that physical activity through football can affect the self-confidence of people with HIV-positive. Keywords: Physical Activity, Football, Self-Confidence, HIV-Positive